Polycystic Ovary Syndrome and Risk of Five Common Psychiatric Disorders Among European Women: A Two-Sample Mendelian Randomization Study - Jin, Luyang; Yu, Jia'en; Chen, Yuxiao; Pang, Haiyan; Sheng, Jianzhong; Huang, Hefeng (Frontiers in Genetics, 2021)
Background: Observational studies have implied an association between polycystic ovary syndrome (PCOS) and psychiatric disorders. Here we examined whether PCOS might contribute causally to such disorders, focusing on anxiety disorder (AD), bipolar disorder (BIP), major depression disorder (MDD), obsessive compulsive disorder (OCD), and schizophrenia (SCZ). Methods: Causality was explored using two-sample Mendelian randomization (MR) with genetic variants as instrumental variables. The genetic variants were from summary data of genome-wide association studies in European populations. First, potential causal effects of PCOS on each psychiatric disorder were evaluated, and then potential reverse causality was also assessed once PCOS was found to be causally associated with any psychiatric disorder. Causal effects were explored using inverse variance weighting, MR-Egger analysis, simulation extrapolation, and weighted median analysis. Results: Genetically predicted PCOS was positively associated with OCD based on inverse variance weighting (OR 1.339, 95% CI 1.083-1.657, p = 0.007), simulation extrapolation (OR 1.382, 95% CI 1.149-1.662, p = 0.009) and weighted median analysis (OR 1.493, 95% CI 1.145-1.946, p = 0.003). However, genetically predicted OCD was not associated with PCOS. Genetically predicted PCOS did not exert causal effects on AD, BIP, MDD, or SCZ. Conclusions: In European populations, PCOS may be a causal factor in OCD, but not AD, BIP, MDD, or SCZ.